Evaluation of Perinatal and Maternal Complications Type of Deliveries and Neonatal Outcomes in Macrosomic and Normal Weighed Newborns in Our Clinic Between 2000 and 2010 Years - Aka, Nurettin; Etiz Sayharman, Sema; Yaşlak, Yasemin; Köse, Gültekin; Tüfekçi, Can (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: The aim of this study was to evaluate the perinatal and maternal complications, the type of the deliveries and neonatal outcomes in the patients whose newborns were weighing 4000gr and above (macrosomic) and between 2500-3999gr (normal). STUDY DESIGN: This retrospective study was done based upon the records of the patients who had given birth between 01.01.2000 and 31.06.2010 in Department of Obstetrics in Haydarpasa Numune Education and Research Hospital. There were totally 9406 patients. We included 1331 patients to our study. In the study group (n=684) the newborns were weighing 4000 gr and above (macrosomic) and in the control group (n=647), who were selected randomly, the newborns were weighing 2500-3999gr (normal). The patients who had given birth before 37 weeks, the multiple gestations and intrauterin growth restricted babies were excluded from the control group. RESULTS: Of the 684 macrosomic newborns, 566 of them (82.7%) were 4000-4499 gr, 104 of them (15.2%) were 4500-4999gr and 14 of them (2.1%) were 5000gr and above. Maternal complications were seen 24.4% in the study group, whereas 7.7% in the control group. CONCLUSION: The risk of perinatal morbidity, maternal complications, birth trauma and neonatal complications were higher in the study group than in the control group. And this was statistically significant (p=0.0001).